Perceptions of faculty teaching anatomy online during COVID-19, A Qualitative study - Ayesha Haque, Ayesha Naveed, Muhammad Imran Ashraf, Ayesha Ghassan, Tayyeba Iftikhar Mirza (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: This study is designed to understand the views of the faculty involved in teaching anatomy using online platforms during recent covid-19 pandemic. An insight into their experiences may help policy makers to improve online sessions of anatomy in the future. Study design: Qualitative phenomenological study Place and duration of study: From September to December 2021 at Dental College, HITEC-IMS. Materials & methods: Semi structured interviews were conducted face to face and transcribed verbatim. All responses were subjected to qualitative analysis, and themes were derived. Results: A total of 15 female participants from three institutions gave feedback. One of the main themes identified was Teaching effectiveness with subthemes including, included Disconnection, feeling ineffective, Technological issues, administrative issues, student related issues, internet issues. Second theme was Opportunities with subthemes including professional development, logistics, blended learning. Third theme was continuing development of online teaching which had subcategories of teacher training, student motivation and connectivity. Conclusion: The study highlights the issues faced by the faculty, teaching anatomy online for the first time during a pandemic. The feedback about learning opportunities gained and advice for future teaching may help inform policy makers of curricular reforms regarding blended learning in future teaching of anatomy.